2008
DOI: 10.1038/jp.2008.184
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric and anatomical MRI for hypoxic–ischemic encephalopathy: relationship to hypothermia therapy and neurosensory impairments

Abstract: ObjectiveTo relate volumetric MRI findings to hypothermia therapy and neurosensory impairments.Study DesignNewborns ≥ 36 weeks’ gestation with hypoxic-ischemic encephalopathy who participated in the NICHD hypothermia randomized trial at our center were eligible. We determined the relationship between hypothermia treatment and usual care (control) to absolute and relative cerebral tissue volumes. Further, we correlated brain volumes with death or neurosensory impairments at 18 to 22 months.ResultsBoth treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…7, 8, 45 Axonal injury assessed by βAPP staining is present in white matter of neonates who suffered birth asphyxia, 46 and WMI was observed in a neonatal pig model of HIE. 47 MRI studies suggest that changes in axonal microstructure accompany early myelination of cerebral white matter.…”
Section: Discussionmentioning
confidence: 98%
“…7, 8, 45 Axonal injury assessed by βAPP staining is present in white matter of neonates who suffered birth asphyxia, 46 and WMI was observed in a neonatal pig model of HIE. 47 MRI studies suggest that changes in axonal microstructure accompany early myelination of cerebral white matter.…”
Section: Discussionmentioning
confidence: 98%
“…This approach employed manual segmentation of subcortical structures, that was built on works published earlier [67,68]. The manual annotation delineated nine structures, namely the cerebellum, brain stem, amygdalae, hippocampus, accumbens, corpus callosum, thalamus, caudate and lenticular nuclei.…”
Section: Authors Validation Metricsmentioning
confidence: 99%
“…88 Finally, a study of volumetric and anatomic magnetic resonance imaging in a subset of 14 patients from the NICHD cooling study showed that infants treated with hypothermia therapy had increased volume of subcortical white matter compared to controls. 89 …”
Section: Physiologic Effects Of Hypothermiamentioning
confidence: 99%